2020
DOI: 10.38057/bifd.690982
|View full text |Cite
|
Sign up to set email alerts
|

Finans ve Bankacılık Sisteminde Yapay Zekâ Kullanımı: Kullanıcılar Üzerine Bir Uygulama

Abstract: Finans sektöründe yapay zekâ uygulamalarının, bireylerin ödeme, tasarruf, birikim gibi alışkanlıkları üzerinde ne kadar etkili olduğunu ölçebilmek amacıyla gerçekleştirilen çalışmada öncelikle; finans sektörünün önemli kuruluşlarından biri olan bankaların tanımı, işlevleri, fonksiyonları anlatılmıştır. Çalışmada, yapay zekâ kavramı tanımlanmış ve finans sektöründe yapay zekânın işleyişi incelenmiştir. Yapay zekâ kullanımı finans sektöründe, maliyetleri azaltması, işlemlerin çabuk gerçekleştirilmesi, sunduğu gü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Moșteanu (2019) addressed the issue of minimizing human error by keeping up with the digital age in financial markets. Researching the use of artificial intelligence in finance and banking, Gümüş et al (2020) concluded that the increase in age, income and education levels is directly proportional to the trust in artificial intelligence. Malali and Gopalakrishnan (2020) conducted a study to strengthen the customer experience by examining the artificial intelligence elements in this sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moșteanu (2019) addressed the issue of minimizing human error by keeping up with the digital age in financial markets. Researching the use of artificial intelligence in finance and banking, Gümüş et al (2020) concluded that the increase in age, income and education levels is directly proportional to the trust in artificial intelligence. Malali and Gopalakrishnan (2020) conducted a study to strengthen the customer experience by examining the artificial intelligence elements in this sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yapay zeka teknolojileri ile bir bankacılık hizmetini müşteriye sunmak veya bankacılık alanındaki pazar bilgilerini toplama işlevleri gerçekleşebilir Bankalarda kullanılan bu yapay zeka uygulamaları genellikle bankanın imajının artmasına destek sağlar. Bu destek ile müşterilerden olumlu geri bildirim alma ve yeni müşterileri bankaya kazandırma prensibi ön planda olur [68].…”
Section: H Bankacılık Alanında Yapay Zeka Etiği Ve Sorunlarunclassified
“…The study, nevertheless, emphasizes cost savings arising from the use of AI. Gümüş et al (2020) surveyed a sample of 500 people and found out that as the age, income and education level of the people participating in the survey increase, the confidence in artificial intelligence increases, too. It has also been concluded that the effective use of Artificial Intelligence in the financial sector provides excellent convenience for users.…”
Section: Literature Reviewmentioning
confidence: 99%